2015
DOI: 10.1093/cvr/cvv202
|View full text |Cite
|
Sign up to set email alerts
|

Transmural APD gradient synchronizes repolarization in the human left ventricular wall

Abstract: The intrinsic transmural difference in APD compensates for the normal cardiac activation sequence, resulting in more homogeneous repolarization of the left ventricular wall. Our data suggest that the transmural repolarization differences do not fully explain the genesis of the T wave.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 37 publications
(47 reference statements)
3
42
0
Order By: Relevance
“…This technique has been extensively used by others in wedges from explanted human hearts 17, 18, 19, 20, 21, 22. Briefly, wedges of porcine myocardium were dissected from the mid apico‐basal region adjacent to the anterior infarct, a region known to support post‐MI arrhythmias.…”
Section: Methodsmentioning
confidence: 99%
“…This technique has been extensively used by others in wedges from explanted human hearts 17, 18, 19, 20, 21, 22. Briefly, wedges of porcine myocardium were dissected from the mid apico‐basal region adjacent to the anterior infarct, a region known to support post‐MI arrhythmias.…”
Section: Methodsmentioning
confidence: 99%
“…Other studies using optical and electrical mapping have demonstrated that the transmural repolarization gradient is small and cannot entirely account for the duration of the T-wave (Anyukhovsky et al, 1999;Boukens et al, 2015;Janse et al, 2011;Meijborg et al, 2014;Rodriguez-Sinovas et al, 1997). Furthermore, recent studies in human left ventricular wedge preparations did not show a subpopulation of M-cells Glukhov et al, 2012;Glukhov et al, 2010;Ng et al, 2014).…”
Section: Transmural Gradients In Repolarization: Where Are the M-cells?mentioning
confidence: 96%
“…While access to animal tissues is typically plentiful, the availability of human cardiac samples is limited. When available, human tissues have typically been limited to fixed or frozen samples or very small amounts of fresh and viable tissues which were obtained from surgical discards (Boukens et al, 2015; Jost et al, 2005, 2013; Brandenburger et al, 2015; Näbauer, Beuckelmann, Überfuhr, & Steinbeck, 1996; Näbauer & Kääb, 1998; Wettwer et al, 1993; Wettwer, Amos, Posival, & Ravens, 1994). However, in the past, tissue recovery procedures, as well as tissue quality and quantity have been extremely variable, resulting in an unreliable source for robust and reproducible drug safety data.…”
Section: Introductionmentioning
confidence: 99%